XML : your visual blueprint for building expert Web sites with XML, CSS, XHTML, and XSLT - Huddleston, Rob. (Hoboken, N.J. : Visual : John Wiley [distributor], 2008)
Provides information on more than one hundred XML techniques, covering such topics as generating XML using Access or Excel, looping and sorting with XSLT, changing font and text color with CSS, debugging with Firebug, and converting XML to XHTML using Dreamweaver.
Includes index.
Keywords: XML (Document markup language); Web sites -- Design